Relationship between Leptin gene and some production traits in local Awasi sheep - E.K, AL-Zargani; N.N, AL-Anbari (Journal of Kerbala for Agricultural Sciences, 2017)
This study had been conducted in the First Research Station for Agriculture College Muthana University and the laboratory of biological technique & practical analysis - Ministry of Science and Technology through the period 1/11/2015 to 1/07/2016. The aims of this study was to determine the genetic components of Leptin gene and explore the relationship of these components with a some of production for local Awasi sheep. The Genotypes had been different to the targeted coding area for Leptin gene according to the variation of the genetic packs that produced by the enzymatic digestion which had reached three genotype who are AA, AB and BB and their distribution ratios were 50.00, 43.33 and 6.67% respectively, and the variation between these ratios was highly significant, and the allele frequency was 0.72 and 0.28 for the allele A and B in series. The current study results shown that total milk production for Awasi sheep had been significantly affected (P<0.05) by the genotypes of Leptin Gene for the sheep that had pure genotype AA, as for milk period duration it had not been significantly affected by genotype variation. The fate and non-fate solid ratios had been significantly influenced where it had been at maximum in sheep’s milks that had the genotype BB (6.79 ±1.34%) and AB (11.05 ± 0.29%) for both parameters in series, while lactose and protein ratios had not been significantly affected by the genotype variation. It can be concluded through the study of the genotype of Leptin gene and its future it adoption to set the genetic rehabilitation strategies for sheep to maximize their economic income of sheep genotype selection and interaction breading projects which already achieved best economic parameters, Additionally, the application of this study on larger sample for many production seasons can give more accurate results to adopt exclusion and replacement strategy.